Hand function and recurrence after limited fasciectomy for Dupuytren's contracture: Long-term follow-up. (12th March 2018) - Bergovec, Marko; Jelicic, Josko; Oljaca, Ana; Bilic, Ranko
Purpose: The aim of this study was to analyze long-term results after limited fasciectomy for Dupuytren's contracture. Methods: The study included 34 patients (52 rays), with an average follow-up of 9.5 years (range: 7–13 years). Range of motion, functional status, recurrence, and complications were recorded. Results: Preoperative metacarpophalangeal joint (MCPJ) contracture (median: 35°, range: 0–90°) improved postoperatively to full extension in all but one patient, with no recurrence at the most recent follow-up. Preoperative proximal interphalangeal joint (PIPJ) contractures (median: 52°, range: 5–100°) were initially corrected, but recurred with time (median: 25°, range 0°–80°). Hand function was assessed using the Disabilities of the Arm, Shoulder and Hand questionnaire. Postoperative hand function improved (median: 0, range: 0–27), compared to preoperative function (median: 20, range: 0–51). Hand function worsened with time (at most recent follow-up: median: 3, range: 0–40), mainly due to PIPJ contracture recurrence, but function remained better than before surgery. Conclusion: Limited fasciectomy is an effective treatment method for MCPJ, with full correction achievable in both the short and long term. Regarding the PIPJ, treatment outcomes seem to be multifactorial. Further clarification is required to distinguish between local recurrence and remaining contracture of the PIPJ.